Evaluation of miRNA detection methods for the analytical characteristic necessary for clinical utilization - Krepelkova, Iveta; Mrackova, Tereza; Izakova, Jana; Dvorakova, Barbora; Chalupová, Lenka; Mikulik, Robert; Slaby, Ondrej; Bartos, Milan; Ruzicka, Viktor (BioTechniques, 2019)
miRNAs are promising biomarkers but methods for their measurement are not clear. We therefore examined three miRNA detection technologies and considered the analytical characteristics essential for clinical utilization. TaqMan assays, SplintR-qPCR and miREIA were compared for their absolute quantification bias, conformity and robustness. Absolute concentrations of miR-142-5p, miR-23a-3p and miR-93-5p were measured with all three methods using 30 samples. Robustness was evaluated by measurement of miR-21-5p in five uniform experiments. Correlations were miRNA-specific, but we observed a different absolute concentration range in RT-qPCR (fmol/μl) and methods evading the RT process (amol/μl). Consistently, RT-less methods reported better robustness (CV 8-19%) than RT-qPCR (CV 39-50%). The calibration curve in TaqMan Advanced assay was influenced by dilution media. Methods avoiding RT seem to be a promising future alternative for miRNA measurement.
Keywords: Neoplasms; nádory; Biomarkers, Tumor; MicroRNAs; lidé; nádorové biomarkery; kvantitativní polymerázová řetězová reakce; mikro RNA; Real-Time Polymerase Chain Reaction; Humans